Interface microstructure of diffusion bonded austenitic stainless steel and medium carbon steel couple - Kurt, B.; Orhan, N.; Ozel, S. (Maney Publishing, 2007)
In the present study, an austenitic stainless steel and medium carbon steel were diffusion bonded. The effect of bonding temperature on microstructural changes and shear strength across the joint region was investigated by optical and scanning electron microscopy, energy dispersive spectroscopy and microhardness measurements. The results showed that the best joint free from microcrack and micovoids was obtained at 900 degrees C with maximum shear strength of 475 MPa.
Keywords: austenitic stainless steel; medium carbon steel; diffusion bonding; interface microstructure